Moonlighting and Teachers’ Job Performance in Public Primary Schools in Selected Local Government Areas, Ogun State, Nigeria - ADERANTI, Ruth A.; OSHO, Oluwaseyi; WILLIAMS, Taiwo M. (Ilorin Journal of Education, 2023)
The performance of pupils in Nigerian public primary schools in which the majority of them cannot read is a reflection of the performance of their teachers. This has constituted a source of concern for all stakeholders in the Nigerian educational system. This study, therefore, adopted a descriptive survey research design to investigate the impact of moonlighting on teachers’ job performance in public primary schools in a selected Local Government Area, Ogun State. Participants for this study consist of 150 primary school teachers selected from the population of 538 from 62 public primary schools using a simple random sampling technique. Data was collected using a self-structured questionnaire. Data collected were analysed using an independent sample t-test and multiple regression analysis for the three hypotheses. The findings revealed no significant gender difference in moonlighting among public primary school teachers, with a t-cal of 0.257 and p-value>0.05(0.797). However, a significant difference exists between moonlighting of unmarried and married public primary school teachers with a higher t-cal of 2.821 and p-value< 0.05 (0.005). Furthermore, the regression analysis results showed that moonlighting significantly influenced teachers’ job performance in public primary schools with F (3, 146) = 317.654, p< 0.05, R2= 0.867. The study conclusively clarified that moonlighting significantly impacted teachers’ job performance. It was therefore recommended that the government put in place motivational techniques to minimise moonlighting among teachers so that they can be more focused on the assigned job.